Vorausschätzungen für die Entwicklung der Gesamtbevölkerung und der Beschäftigung in Österreich bis 2035 - Kai Biehl; Thomas Fent (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2007)
– This paper investigates the future development of the Austrian population for the period from 2005 to 2035. The main focus of our investigation lies on the working age population and its age structure. Our calculations are based on the population projection released by Statistik Austria in 2005. We present three different scenarios with respect to age specific labour force participation rates and discuss their impact on the Austrian labour force. We show that both the main variant and the low migration variant of the population projection allow for an annual increase in the total size of labour force of 0.3% until the end of our observation period by applying labour force participation rates which are already put into practice in the Nordic countries. An increase in labour force participation rates does not only help to maintain an increase in the labour force but also leads to a more homogenous age distribution of the labour force.
Keywords: 300; Ageing; age structure; labour force; labour force participation rates; Bevölkerungsprognose; Altersstruktur der Bevölkerung; Arbeitskräftepotenzial; Österreich